A new type of tattoo - Canter, Neil (Tribology & lubrication technology, 2014)
Wenzhao Jia, Joseph Wang, distinguished professor and chairperson of the nanoengineering department at the University of California-San Diego, and their associates have harnessed the energy from sweat by developing a biofuel cell that is powered by a substance found in sweat, lactate. To deal with the problem of keeping the biofuel cell on the human body so that it is comfortable to the user and does not come off, the researchers developed a temporary transfer tattoo. They have described the technology as a temporary transfer tattoo biofuel cell or tBFC. The effectiveness of the tBFC was first evaluated over a four-week period by using artificial sweat. The tBFCs performed well in all cases, and all human subjects reported no discomfort, no skin irritation and no inflammatory responses to the devices. Power generation was found to be dependent upon the fitness level of the individual. Higher power levels were seen with less fit individuals who needed to produce higher levels of lactate during exercise.